Effects of Low Dose X-Ray Irradiation on Porcine Articular Cartilage Explants - Lindburg, C. Alexander (2013)
Ionizing radiation therapy is a crucial treatment for cancer, but can damage surrounding normal tissues. Damage to articular cartilage leading to arthropathy can occur at irradiated sites. It is unclear whether this response is due to damaging surrounding skeletal structures or direct effects on cartilage. In this study, we showed that irradiation with 2 Gy of X-rays causes a significant reduction in the stiffness of porcine explants 1 week post-irradiation. By using both microindentation and indentation-type atomic force microscopy, ionizing radiation reduces stiffness in both the superficial zone and throughout the entire thickness of the tissue. Young’s modulus values were 75% and 60% lower in 2 Gy irradiated samples when compared with controls using microindentation and nanoindentation, respectively. Glycosaminoglycans (GAGs) released into the culture media of irradiated samples was nearly 100% greater at 24 hours after exposure. While collagen content in the tissue is similar between groups, GAG content is 55% lower in irradiated explants compared with controls by one week. Therefore, the irradiated explants are unable to recover from the initial loss of GAGs by one week. This acute loss of GAGs is a likely contributor to the reduction in modulus seen after exposure to ionizing radiation.